Extraction and characterization of a novel natural lignocellulosic (bagasse and husk) fibers from arrowroot (Maranta arundinacea) - Tarique, Jamal; Salit, Mohd Sapuan; Abdan, Khalina (Taylor & Francis, 2022)
This study set out with the aim of assessing the morphology and properties of lignocellulosic fiber extracted from the tubers mainly found in tropical forests called arrowroot (Maranta arundinacea). Arrowroot bagasse (ABF) and husk fibers (AHF) were extracted and the physical, chemical, thermal, morphological properties, as well as crystallinity, were characterized. The chemical composition analysis revealed that ABF has higher cellulose (45.97%) than AHF (37.35%), cassava bagasse (10.04%), and corn hull (15.30%). In addition, ABF are significantly low in lignin (2.78%) and density (1.11 g/cm3) than AHF, corn hull, and cassava. In this research, the physical, chemical, thermal, structural, and morphological properties of arrowroot bagasse and husk fibers were investigated by particle size analysis, chemical composition analysis, thermogravimetric analysis (TGA), Fourier transform infrared (FTIR) and scanning electron microscopy (SEM), respectively. With respect to the above characterization of fibers, it was found that the lignocellulosic biomasses from arrowroot are alternative promising sustainable material, which can be used in food packaging as a renewable filler.